Management of an inflammatory abdominal aortic aneurysm causing ureteric obstruction: a case report - Kim, Yewon (J Surg Case Rep, 2020)
Inflammatory abdominal aortic aneurysms (IAAAs) are rare large-vessel pathology, with potentially life-threatening complications including obstructive uropathy secondary to retroperitoneal fibrosis. Comprising a small proportion of all AAA, their pathogenesis remains unknown, with the hypothesis of infective and immunological aetiologies circulating in current literature. Management principles of IAAAs aim at prevention of aortic rupture and include open-surgical or endovascular therapies. Due to their involvement of other structures, additional considerations are needed when approaching their management for optimal patient outcomes. We present the case of a 53-year-old otherwise healthy male with a large IAAA complicated by adjacent ureteric obstruction, successfully treated with ureteric stenting and delayed endovascular aortic aneurysm repair.